Islam in Indonesia - Jajat Burhanudin, Kees van Dijk (Amsterdam University Press, 2013)
In recent years, the way Islam manifests itself in Indonesia has changed. As elsewhere in the Muslim world, there is stricter adherence to Islam, and fundamentalism has gained strength. An increasing number of Indonesian Muslims are observing the tenets of their religion more faithfully. More people fulfil the hajj, one of the basic pillars of Islam, and an increasing number of women wear a headscarf, sometimes a very fashionable one. These women include members of a segment of society that used to be considered the embodiment of secularism and syncretism, known in Indonesia as the abangan. National surveys confirm this trend. In the last ten years or so, Muslims in Indonesia have become more religious in their attitudes and practices. The use of rituals associated with abangan culture has decreased, to be replaced by those of more observant Muslims, the santri. As a result, Islamic symbols and elements can be seen everywhere in Indonesian public life, including in liberal and capitalist institutions such as company offices and shopping malls. The increasing emphasis on Islam is also reflected in the shifting position of fundamentalist groups. Since Suharto was forced to step down in the late 1990s, Indonesia has witnessed a growing religious militancy. Not only have the militants increased in number, but they are also more actively engaged in missionary activities among fellow Muslims. Various radical organisations have emerged, including the FPI (Front Pembela Islam, Front of the Defenders of Islam), the MMI (Majelis Mujahidin Indonesia, Indonesian Council of Jihad Fighters) and the Laskar Jihad (Jihad Force). With a militant agenda of purifying Islam, these organisations are engaged in a series of violent acts against others, creating concern among moderate Muslims, who still form a majority in Indonesia. Their aspiration is to implement Islamic law in the public sphere, which in Indonesia is supposed to be religiously neutral